The baskets and the basket-makers of prehistoric south-east Europe: a palaeoethnobotanical approach - Mila, Andonova (2020)
Archaeological basketry is one of the ‘invisible’ types of material culture, which in South-east Europe are rarely preserved, and hence rarely properly recorded. Nevertheless, in the cases, where basketry remains are retrieved, they are often considered not very informative, as other vegetal remains, such as seeds or charcoal. In addition, this type of material is very challenging when botanically identified, mainly due to its high fragility, demanding preservation and not adequate conservation. This thesis will attempt to reveal the ‘invisibility’ of archaeological basketry in the study region of South-east Europe, via an integrated approach, including established and novel techniques for the assessment and identification of botanical remains, in combination with field ethnographic work, access to museum archive material and reference no supportive proxies as palaeoenvironmental data, iconography and aspects of materiality. This multi-proxy approach highlights the high informative potential of archaeological basketry and perhaps, it will encourage future studies on the subject.